Why Students are Cool to Internal Assessment? A study of the behavior of students of Koteshwar Multiple Campus (KMC) - Nepal, Dhruba (KMC Research Journal, 2017)
Internal assessment is applied for learning achievement but it has been found that as the level of academic level and year increase, student’s appearance in internal assessment shows declining trend. To find out the reasons, a small study based on qualitative data conducted. The underlying causes of cool behavior towards internal assessment is complacency to get through final examination instead of excelling, engagement with earning activities that mismatch with campus schedule teaching and assessment and girl students get married and pregnant as their age grow.